Effect of ultraviolet illumination and ambient gases on the photoluminescence and electrical properties of nanoporous silicon layer for Organic Vapor Sensor - Atiwongsangthong, Narin (My University, 2012)
The purpose of this research, the nanoporous silicon layer were fabricated and investigated the physical properties such as photoluminescence and the electrical properties in order to develop organic vapor sensor by using nanoporous silicon. The Changes in the photoluminescence intensity of nanoporous silicon samples are studied during ultraviolet illumination in various ambient gases such as nitrogen, oxigen and vacuum. In this paper, the nanoporous silicon layer was used as organic vapor adsorption and sensing element. The advantage of this device are simple process compatible in silicon technology and usable in room temperature. The structure of this device consists of nanoporous silicon layer which is formed by anodization of silicon wafer in hydrofluoric acid solution and aluminum electrode which deposited on the top of nanoporous silicon layer by evaporator. The nanoporous silicon sensors were placed in a gas chamber with various organic vapor such as ethanol, methanol and isopropyl alcohol. From studying on electrical characteristics of this device, it is found that the nanoporous silicon layer can detect the different organic vapor. Therefore, the nanoporous silicon is important material for organic vapor sensor and it can develop to other applications about gas sensors in the future. Copyright © 2012 American Scientific Publishers.
Keywords: Anodization; Nanoporous Silicon; Organic Vapor Sensor